Patterns of postgraduate transitions amongst care-experienced graduates in the United Kingdom. Issue 3 (4th May 2022) - Baker, Zoe; Harrison, Neil; Stevenson, Jacqueline; Wakeling, Paul
ABSTRACT: Those who have spent time in state care as children, and are therefore 'care-experienced', are known to have lower life chances than the general population. While we know that care-experienced young people are significantly underrepresented in Higher Education nationally and internationally, little is known about their progression to postgraduate level study. Using data from the national Destinations of Leavers from Higher Education (DLHE) survey, this paper explores patterns of postgraduate progression for care-experienced graduates in the United Kingdom. As postgraduate qualifications have been found to provide numerous benefits, this is important to understand; these benefits could be particularly transformative for those with care experience – mitigating their background disadvantages. The authors' data present a positive picture, showing that care-experienced graduates who successfully access and complete an undergraduate degree are significantly more likely to progress to postgraduate study than non-care-experienced graduates. We propose explanations for these findings, and make recommendations for practice to establish further equality in these patterns of progression.